Comparative evaluation of phenotypic, pedigree, and family-based selection in insect breeding using stochastic simulation - L.S. Hansen; A.C. Bouwman; G. Sahana; M. Slagboom; H.M. Nielsen; E.D. Ellen (Animal)
Selective breeding in insects has predominantly relied on phenotypic selection without considering relatedness. Selection on estimated breeding values could potentially increase genetic gain, but the challenge of pedigree tracking complicates this. Family selection can be used as an alternative to individual selection, either using combined between- and within-family selection, or strict between-family selection with full-sib group records as a proxy for individual data. The effectiveness of family selection can however be compromised by the presence of unmitigated common environmental effects. In this study, we employ stochastic simulations to explore expected genetic gain and rate of inbreeding in insect populations under four single-trait selection schemes: phenotypic selection, individual pedigree selection, combined selection using both family and individual breeding values for selection, and between-family selection using full-sib average phenotypes for breeding value estimation. These schemes are compared on genetic gain and rate of inbreeding across five trait heritabilities (0.05, 0.1, 0.2, 0.4 and 0.6), two variations in number of families in the population (60 or 200), and two offspring group structures for the family breeding schemes (1 or 3 sib groups per female) with a fixed common environment effect. Selection based on individual breeding values results in significantly higher genetic gain than phenotypic selection at low heritability (≤ 0.1), and similar gain at heritability > 0.1. Phenotypic selection results in a lower rate of inbreeding (0.003–0.011) compared to other schemes (0.005–0.055) at low heritability (≤ 0.1), but this difference is reduced as heritability increases. Combined selection results in genetic gain between that of the phenotypic and individual pedigree schemes, depending on sib group structure and heritability. Using between-family selection reduces genetic gain (0.23–1.97) compared to other schemes (0.40–4.34). Establishing multiple sib-groups mitigates the confounding of genetic and common environment effects, and thus the reduction in genetic gain from family selection schemes. Increasing the number of families from 60 to 200 in the breeding population reduces inbreeding in all scenarios (ΔF at 60 families is 0.009–0.055, at 200 families is 0.003–0.031). We conclude that selection on individual breeding values yields greater genetic gain compared to family breeding values and selection on phenotypes. The between-family approach is an alternative when individual pedigrees are not feasible to maintain. Phenotypic selection results in both high genetic gain and generally low rates of inbreeding, but as heritability increases, so does the rate of inbreeding. Therefore, phenotypic selection should not be implemented without any inbreeding control in long−term selection.